COVID-19 and higher education: responding to local demands and the consolidation of e-internationalization in Latin American universities - Miguel Cordova; Dinorá Eliete Floriani; Maria Alejandra Gonzalez-Perez; Michel Hermans; Santiago Mingo; Fabiola Monje-Cueto; Karla Maria Nava-Aguirre; Carlos Adrian Rodriguez; SALVAJ CARRERA, ERICA HELENA (My University, 2021)
PurposeThis paper aims to provide insights into the internationalization strategic responses to the COVID-19 pandemic by higher education institutions (HEIs) in Latin America.Design/methodology/approachThis study is based on information from eight leading Latin American private universities. The data were obtained from official sources such as institutional communications and university administrators.FindingsThe authors identify two main issues that HEIs should consider while responding to the pandemic. First, greater attention and resource allocation to the universities' main local stakeholders can affect traditional internationalization activities. Second, a focus on revitalizing foreign partnerships and strengthening “virtual internationalization” can help maintain and eventually increase international presence.Research limitations/implicationsWhile this study analyses how these Latin American HEIs responded during the initial stages of the COVID-19 outbreak, it is important to conduct follow-up studies to shed light on how HEIs are adapting to the COVID-19 crisis as it continues to unfold.Originality/valueThis study is based on unique information gathered from leading private, not-for-profit HEIs in Latin America, which, contrary to state-owned HEIs or other private institutions in developed economies, have exhibited different means and conditions to respond to the coronavirus outbreak. Finally, the authors contribute to the literature on the internationalization of HEIs by discussing the role of a significant disruptive event on the internationalization of higher education and, particularly, business schools.
Keywords: higher education institutions; latin america; covid-19; global crisis; online learning; e-internationalization; instituciones de educacion superior; america latina; covid-19; crisis global; aprendizaje en linea; e-internacionalizacion